Óxidos libres de hierro y aluminio en suelos tropicales - BORNEMISZA, E.; Igue, K. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
"Methods are proposed to determine the "free" iron and aluminum content of soils in the tropics. The content of these oxides was determined in samples from the plow layer of 10 soils and in samples from the A and B horizons corresponding to 16 soils. The samples were taken in Brazil, Colombia, Costa Rica, Panama and Peru, and include latosols (11), alluvial soils (12), andosols (2) and a "terra roxa" from Brazil. Almost two thirds of the soils studied contained more than 14% of R2O3, and about one eighth of them more than 25%. Free aluminum oxide varied most, having values between 13% and 20.6%, while the free iron oxide data were between 0.9% and 11.8%. Average free Fe2O3 for the latosols was 6.7% while free Al2O3 was 11.7. A large variation was noted for alluvial soils. The andosols were high in Fe2O3 (58% av.) and even higher in Al2O3 (17.3% av.)